Structure and content of quasi-professional experience - Synevych Inna (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2019)
The content of quasi-professional activity of future teachers of Musical Arts has been disclosed. It has been determined that students’ formation of quasi-professional activity through their quasi-professional activity within the educational process provides the modelling of situations where future specialists can practice in successful implementation of educational functions of the teacher on the basis of gained knowledge and experience. It has been noted that the process of quasi-professional experience formation also contributes to the growth of the creative and cognitive activities, stability of students’ professional motivation providing the development of their positive, value-centre attitudes towards the profession of the Music teacher. The structure of the quasi-professional experience of the future teachers of Musical Arts has been disclosed, the main structure components have been determined, in particular, professional and reflexive, activity-centred and creative, value-centred and motivational, emotional and interpretive. The detailed analysis of each structure component has been carried out. It has been emphasized that the formation of the professional-and-reflexive component of the quasi-professional experience provides influence on the motivational value-centred, intellectual, activity-centred spheres as well as on the improvement of professional skills of the future teachers of Musical Arts. The activity-centred and creative components aimed at obtaining knowledge, practical experience of the musical-and-creative, vocational and pedagogical activities by the students as well as developing of their own proficiency have been considered. The value-centred and motivational components which determine vectors of value orientations, stable motivational sphere, provide increased learning efficiency of the future teachers-musicians, activate the need in professional self-realization have been characterized. It has been proved that the emotional and interpretive components are significant components of the quasi-professional experience which enable the students to master professional skills and develop their personal qualities that determine emotional and personal styles as well as to form an image of the Musical Arts teacher, artistry, musical interpretation that substantially influence their further professional activity.